Synergistic Effect of Halloysite Nanotubes and Glycerol on the Physical Properties of Fish Gelatin Films - Qiang, Xiaohu (Polymers (Basel), 2018)
Fish gelatin (FG)/glycerol (GE)/halloysite (HT) composite films were prepared by casting method. The morphology of the composite films was observed by scanning electron microscopy (SEM). The effects of HT and GE addition on the mechanical properties, water resistance and optical properties of the composites were investigated. Results showed that with increasing GE content, the elongation at composite breaks increased significantly, but their tensile strength (TS) and water resistance decreased. SEM results showed that GE can partly promote HT dispersion in composites. TS and water resistance also increased with the addition of HTs. Well-dispersed HTs in the FG matrix decreased the moisture uptake and water solubility of the composites. All films showed a transparency higher than 80% across the visible light region (400–800 nm), thereby indicating that light transmittance of the resulting nanocomposites was slightly affected by GE and HTs.